Characterisation and Isolation of Candida Species from ICU Patients in Nobel Medical College Teaching Hospital, Biratnagar - Chaudhari, Bigu Kumar; Singh, Ganesh K.; parajuli, Kamal Prasad; Shrestha, Kewal; Shah, Dharmendra (Journal of Nobel Medical College, 2016)
Background Fungi have emerged as major causes of human diseases. Intensive Care Units (ICU), harbor almost all the risk factors for opportunistic fungal infections. Among these, Candida infections are very common with recent trends being rise in the non-Candida albicans (NCA) species along with an increase in resistance of these species to antifungal drugs. Increament in invasive Candidasis during last three decades have been reported in several studies, among all Candida species the Candida albicans is considered as the most common infectious agent the other non-albicans like C. Tropicalis, C. glabrata, C. parapsilosis C. krusei, and C. dubliniensis were raised as infectious agents. The aim of current study is to characterize the candida species from the clinical specimens of patients admitted in the ICU of Tertiary Care hospital in Eastren Nepal and to perform their antifungal susceptibility.Material and Methods The study was carried out in the tertiary care hospital Nobel Medical College and Teaching Hospital Biratnagar Nepal over a period of 6 monthsbetween September 2015 to February 2016. The following techniques were employed to characterize the isolates in the study – Gram’s stain, culture on Sabouraud’s Dextrose Agar, Germ Tube test, morphology in Cornmeal Agar and chromogenic agar media, sugar fermentation and sugar assimilation tests, and the results were interpreted by using standard protocols.Results Out of 50 candida isolates from different clinical samples including 37 blood samples, 9 urines and 4 Endo Tracheal (ET) tube, the most common species was C.albicans (44%) followed by C.tropicalis (26%), C.Glabrata (18%), C.Parapsilosis (08%), C.Krusei (02%), and C.Dubliniensis(02%).Conclusion The purpose of the study is to show the value of species isolation, identification and antimicrobial sensitivity testing of the ICU & NICUs patients.Journal of Nobel Medical CollegeVolume 5, Number 1, Issue 8, January-July 2016, 61-65